Implementation of Non Formal Education Programs For Village Communities in Batu City - Putri, Silvy Novita; Saiman, Saiman; Nurjaman, Asep (Journal of Local Government Issues, 2018)
This study aims to explain the program implementation model implemented by the Batu City Education Office for the welfare of people who have low education or even never go to school at all. This study focuses on two things, namely the implementation of non-formal education programs for the community and who are the supporters and inhibitors of the implementation of the program. This study uses descriptive qualitative research methods, using interview techniques. The results of this study indicate that the implementation of the program carried out by the Batu City Education Office for the community has not gone well. This is due to two factors, namely the implementation factors and community factors. The first factor is the implementation factor that lacks commitment in the implementation of the program, less planned in monitoring and evaluating the program. The second factor is the people who are not too enthusiastic in participating in the program provided by the Batu City Education Agency.Keywords: Implementation; Non-formal Education; Society